The Reconstruction of Peripheral Auditory Circuit: Recent Advances and Future Challenges - Zhe Li; Ying Zhang; Zhenyu Xiao; Jieyu Qi (Advanced Science)
Abstract The auditory circuit primarily consists of peripheral auditory organs and auditory neural pathways. Hearing loss (HL), as reported by the World Health Organization, affects more than one in eight people worldwide, often leading to severe dysfunction that detrimentally impacts patients' quality of life. Therefore, auditory reconstruction has emerged as a persistent research hotspot and challenge within the biomedical field. Traditional methods for auditory reconstruction, such as drug therapy, hearing aids, cochlear implants (CIs), and so on. To a certain extent, it can help patients with HL improve their hearing status. However, they possess inherent advantages and limitations. Recent advancements in biomaterials, gene editing, stem cells, organoids, and other technologies have ushered in new prospects for the treatment of hearing impairment. This review focuses on the potential of innovative technologies in biomaterials, stem cells, and gene editing in hearing recovery. It reviews the current research status of inner ear hair cell (HC) regeneration, spiral ganglion neuron (SGN) regeneration, and inner ear organoid construction in the auditory loop. Furthermore, the review discusses the challenges associated with these approaches and explores potential future directions, aiming to furnish a comprehensive reference for both research and clinical applications in the domain of peripheral auditory restoration.